Bermudagrass for Florida Lawns - Laurie E. Trenholm; John L. Cisar; J. Bryan Unruh (EDIS)
Bermudagrasses (Cynodon spp.) are among the most widely used warm-season grasses. Improved, fine-textured bermudagrasses are used throughout the south on golf courses, athletic fields, and in high-profile residential and commercial landscapes where a fine-textured, dense ground cover is desired. This revised 5-page fact sheet describes advantages, disadvantages, cultivars, maintenance, and pest problems. Written by L. E. Trenholm, J. L. Cisar, and J. B. Unruh and published by the UF Department of Environmental Horticulture, March 2011.